Evaluating the efficacy of surgical and conservative approaches in mild autonomous cortisol secretion: a meta-analysis - Ren, Xingxiang; Nan, Min; Zhang, Xiaomei (Frontiers in Endocrinology, 2024)
Abstract Introduction: The management of Mild Autonomous Cortisol Secretion (MACS) remains a topic of debate among clinicians, with differing opinions on the effectiveness of surgical intervention compared to conservative treatment methods. This meta-analysis provides a comprehensive assessment of available literature to determine the most effective approach for treating this condition. Methods: On December 1, 2023, an exhaustive literature search of English databases Embase, PubMed, the Cochrane Library, Scopus, Web of Science, as well as the Chinese databases China HowNet, Wanfang Database, SinoMed Database, and Weipu Database using the keywords “Mild Autonomous Cortisol Secretion”, “Subclinical Cushing's Syndrome”, “Subclinical Hypercortisolism”, “Mild Cortisol Autonomous Secretion”, “Adrenal Incidentaloma”, “Surgical Treatment” and “Adrenalectomy”. The data were statistically analyzed using STATA version 15.0. Results: In this comprehensive analysis involving 629 patients with MACS, the therapeutic efficacy of adrenalectomy was evident. The meta-analysis results indicate that compared to conservative treatment, surgical intervention more effectively improves obesity indicators in patients: waist circumference (SMD=-0.62, 95% CI: -1.06 to -0.18), BMI (SMD=-0.41, 95% CI: -0.62 to -0.20), enhances glycemic control: fasting blood glucose (SMD=-0.47, 95% CI: -0.68 to -0.26), glycated hemoglobin (SMD=-0.66, 95% CI: -0.95 to -0.38), improves lipid metabolism: triglycerides (SMD=-0.45, 95% CI: -0.73 to -0.16), lowers blood pressure: systolic blood pressure (SMD=-1.04, 95% CI: -1.25 to -0.83), diastolic blood pressure (SMD=-0.89, 95% CI: -1.12 to -0.65), and ameliorates hormonal metabolic disorder: 24h urinary free cortisol (SMD=-1.10, 95% CI: -1.33 to -0.87), ACTH (SMD=2.30, 95% CI: 1.63 to 2.97). All these differences are statistically significant. Conclusion: This meta-analysis shows that, compared to conservative treatment, surgical treatment is more effective in improving obesity indicators, glycemic control, lipid metabolism, reducing blood pressure, and ameliorating hormonal metabolic disorders in patients with MACS. These statistically significant results highlight the importance of considering surgical intervention in the management of patients with MACS. Keywords: Mild Autonomous Cortisol Secretion, Metabolic disorder, Adrenalectomy, Conservative Management, Meta-Analysis